PENGARUH PENGUMUMAN DIVIDEN ERHADAP PERUBAHAN HARGA SAHAM SEBELUM DAN SESUDAH EX-DIVIDEND DATE DI BURSA EFEK INDONESIA - Sudiarto, Haryo (Universitas Muhammadiyah Magelang, 2007)
Dividend represent the value of net earning company after lessened by the lease with the retained earning which is used as by a company reserve. Intention of research condusted this is to know the price change of share that happened when period of before and after Ex-dividend date which is because of dividend announcement. This research represent the event study with the approach of case study of at Indonesia Stock Exchange using historical data of year 2004-2006. Sample in this research is as much 45 company. Sample will be taken by purposive sampling and company in Indonesia Stock Exchange. Analysis used in this research is One Sample t-test. Pursuant analysis conducted, commonly company of increase devident, knowable that at t-2 period, t-1 period, t0 period, t-5 period of announcement deviden, causing share price experience of the change which significant, natural company of degradation deviden, knowable that at t-2 period, t-1 period, t0 period, t-5 period of announcement deviden, causing share price experience of the change which significant. This matter is market with the result existence which significant of among day of before and after ex-devident date.